2018
DOI: 10.2147/ccide.s165377
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo decontamination of yeast-colonized dentures by iodine–thiocyanate complexes

Abstract: IntroductionUnder well-defined experimental conditions, and in the presence of hydrogen peroxide, lactoperoxidase produces stable iodine–thiocyanate complexes that have antimicrobial properties. A novel process was developed to short circuit the consumption of hydrogen peroxide by microbial catalases by producing iodine–thiocyanate complexes prior to contact with microorganisms, with the aim of being able to decontaminate the ex vivo dentures colonized by yeasts.Materials and methodsTeabags containing lactoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…[9,10]. While studying biological lactoperoxidase activity in the presence of an SCN − /I − mixture, a few articles have addressed the products generated under such and such experimental conditions [11,12,21,27]; several have showed that a more stable oxidative complex was formed in specific pH and ionic strength conditions [25,[27][28][29]. We found OSCN − after LPO oxidation of SCN − and I 2 after LPO oxidation of I − .…”
Section: Influence Of the Substrate Concentrations On Antifungal Actimentioning
confidence: 70%
“…[9,10]. While studying biological lactoperoxidase activity in the presence of an SCN − /I − mixture, a few articles have addressed the products generated under such and such experimental conditions [11,12,21,27]; several have showed that a more stable oxidative complex was formed in specific pH and ionic strength conditions [25,[27][28][29]. We found OSCN − after LPO oxidation of SCN − and I 2 after LPO oxidation of I − .…”
Section: Influence Of the Substrate Concentrations On Antifungal Actimentioning
confidence: 70%
“…Human fungal infections including those caused by yeast and yeast-like fungi constitute a serious burden in Algeria [48][49][50][51][52][53][54][55][56][57]. At least 27 taxa are identified in care controls.…”
Section: Yeasts Within Human Healthmentioning
confidence: 99%
“…neoformans. Only one case mentioned a denture contaminated by C. albicans [57], the ex vivo decontamination of this yeastcolonized denture was realized by iodine-thiocyanate.…”
Section: Yeasts Within Human Healthmentioning
confidence: 99%
“…Mixtures of the two substrates, SCN − and I − , however, appear to lead to the formation of a more stable oxidative complex over time ( 65 , 66 , 87 90 ). Under well-defined in vitro experimental conditions (high ionic strength; KI:KSCN ratio, ~4.5; neutral or acidic buffer; presence of H 2 O 2 ), lactoperoxidase produces stable iodine-SCN − complexes, such as I 2 (SCN) − , objectified by carbon-13 (C13) nuclear magnetic resonance spectroscopy ( 66 ) with antimicrobial properties against Candida ( 67 ). Oxidant concentrations are then less toxic to epithelial cells in the mouth, as compared with chlorhexidine ( 67 ).…”
Section: Oxidant Production By Oral Peroxidasesmentioning
confidence: 99%
“…Under well-defined in vitro experimental conditions (high ionic strength; KI:KSCN ratio, ~4.5; neutral or acidic buffer; presence of H 2 O 2 ), lactoperoxidase produces stable iodine-SCN − complexes, such as I 2 (SCN) − , objectified by carbon-13 (C13) nuclear magnetic resonance spectroscopy ( 66 ) with antimicrobial properties against Candida ( 67 ). Oxidant concentrations are then less toxic to epithelial cells in the mouth, as compared with chlorhexidine ( 67 ). The resistance of epithelial cells may be explained by the presence of bacteria covering their surface and forming a protective biofilm, and/or by the detoxification of enzymatic activities in certain commensal species present in the oral environment ( 91 ).…”
Section: Oxidant Production By Oral Peroxidasesmentioning
confidence: 99%